2012
DOI: 10.1523/jneurosci.3446-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and Extrinsic Mechanisms Control the Termination of Cortical Interneuron Migration

Abstract: During development, neurons migrate from their site of origin to their final destinations. Upon reaching this destination, the termination of their migration is crucial for building functional architectures such as laminated structures and nuclei. How this termination is regulated, however, is not clear. Here, we investigated the contribution of cell-intrinsic mechanisms and extrinsic factors. Using GAD67-GFP knock-in mice and in utero electroporation cell labeling, we visualized GABAergic neurons and analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…Therefore, it is possible that the timing of PlexinD1 downregulation, which controls FLP formation and neuronal migration termination in the OB, is intrinsically programmed in each new neuron or its parental NSC in the V‐SVZ. The timing of migration termination and the subsequent integration of cortical interneurons are also intrinsically determined by cellular age (Bortone & Polleux, ; Inamura et al , ; Southwell et al , ). In contrast, interestingly, our transplantation study showed that the duration and distance of migration are not strictly programmed in each V‐SVZ‐derived new neuron (Fig ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that the timing of PlexinD1 downregulation, which controls FLP formation and neuronal migration termination in the OB, is intrinsically programmed in each new neuron or its parental NSC in the V‐SVZ. The timing of migration termination and the subsequent integration of cortical interneurons are also intrinsically determined by cellular age (Bortone & Polleux, ; Inamura et al , ; Southwell et al , ). In contrast, interestingly, our transplantation study showed that the duration and distance of migration are not strictly programmed in each V‐SVZ‐derived new neuron (Fig ).…”
Section: Discussionmentioning
confidence: 99%
“…Most MGE-derived interneurons in the adult neocortex express either somatostatin (SST) or parvalbumin (PV) (Fogarty et al, 2007;Miyoshi et al, 2007). A majority of these interneurons complete their tangential migration into the neocortex by birth (Miyoshi and Fishell, 2011;Inamura et al, 2012). However, PV protein or Pvalb mRNA is not expressed until much later, indicating that the expression of PV or Pvalb is a useful marker of maturation for this lineage of cells.…”
Section: Parvalbumin-expressing Interneurons In Medial Pfc Respond Tomentioning
confidence: 99%
“…The mechanisms that regulate the expression of KCC2 remain unknown. One possibility is that interneurons turn on KCC2 expression as part of an intrinsic program of maturation (Inamura et al, 2012). This would allow interneurons to cease migration progressively, depending on their birthdate (Hevner et al, 2004;Pla et al, 2006).…”
Section: Stop Signalsmentioning
confidence: 99%